Antagonism between Byssochlamys spectabilis (anamorph Paecilomyces variotii) and plant pathogens: Involvement of the bioactive compounds produced by the endophyte. (29th September 2017) - Rodrigo, S.; Santamaria, O.; Halecker, S.; Lledó, S.; Stadler, M.
Abstract: Fungal endophytes can be part of the defensive system of plants against multiple pathogens by competing for resources, hyperparasitism or producing bioactive compounds with antimicrobial properties. There is an ever‐increasing interest for obtaining new and environmentally friendly products to use in the fight against pathogens. With this purpose, Byssochlamys spectabilis (anamorph Paecilomyces variotii ), which is a fungal species that commonly occurs, was evaluated as an antagonistic organism towards three phytopathogens ( Biscogniauxia mediterranea, Fusarium moniliforme and Phytophthora cinnamomi ). First, an in vitro experiment was designed to test the effect that the endophyte filtrate had on the three pathogens. The endophyte filtrate decreased the radius growth rate of F. moniliforme by nearly 10%. Consequently, the antagonism between B. spectabilis and F. moniliforme was evaluated in Lolium rigidum plants under greenhouse conditions by means of co‐inoculations. The endophyte produced a decrease of 50–75% in the disease severity caused by the pathogen in the earliest infection stages. Crude extracts of B. spectabilis were obtained to determine the secondary metabolites responsible for such an effect. The bioactivity‐guided chromatography and HPLC‐MS (high performance liquid chromatography coupled with mass spectrometry) of the active fraction suggested that the antibiotic activity was caused by viriditoxin. In conclusion, the fungal endophyte B. spectabilis and/or its bioactive compounds showed antagonism towards several phytopathogens and deserves further study to investigate its actual potential for use as a biocontrol agent. Abstract : The fungal endophyte Byssochlamys spectabilis (anamorph Paecilomyces variotii ) showed antagonism towards phytopathogens in vitro and in Lolium rigidum plants. The antibiotic activity seemed to be caused by the secondary metabolite viriditoxin produced by the endophyte